Ethnobotanical Study of Medicinal Plants Used to Treat Human and Livestock Ailments in Hulet Eju Enese Woreda, East Gojjam Zone of Amhara Region, Ethiopia - Abebe, Birhanu Adibaru (Evid Based Complement Alternat Med, 2021)
Indigenous people of a given community have their own local specific knowledge on plant use, management, and conservation. The objective of this study was to document medicinal plants used to treat human and livestock ailments in Hulet Eju Enese Woreda. The data were collected using semistructured interviews, focus group discussions, and field observations with local people. A total of 100 informants over the age of 20 years were selected to collect information on medicinal plant use. Descriptive statistics (percentage and frequency), Jaccard's similarity index, independent sample t-test and analysis of variance, informant consensus factor, fidelity level, preference ranking, and direct matrix ranking were computed. A total of 80 medicinal plant species belonging to 75 genera and 52 families were documented. In terms of species diversity, Solanaceae stood first with 5 species followed by Euphorbiaceae and Malvaceae with 4 species each. Out of eighty medicinal plants, 53 species were used to treat only human ailments, 8 species were used to treat only livestock ailments, and the remaining 19 species were used for treating both human and livestock ailments. From the total medicinal plant species, shrub constitutes the largest number with 42.5% species. The most frequently used plant parts were leaves, accounting for 28.9%. The major routes of administration were oral accounts, 81 (57%), followed by dermal, 45 (31.7%), nasal, 6 (4.2%), and others, 10 (7%). In the disease category with the highest informant consensus factor (0.83) value was sudden sickness. There was highest preference (49) for Phytolacca dodecandra to treat rabies. Cordia africana was shown to be the top multipurpose species. This study revealed that the study area was rich in medicinal plants. Agricultural expansion, charcoal making, and firewood collection were considered major threats to medicinal plants. Therefore, awareness creation to the youth and training to the healers play a pivotal role to prevent the loss of indigenous knowledge.